Carbon Sequestration of Fruit Trees under Contrasting Management Regimes - Muhamud Nabalegwa Wambede; Gertrude Akello; Andrew Mulabbi; Bernard Barasa; Jerome Sebadduka Lugumira; David Amonya (Indonesian Journal of Geography, 2022)
This study aimed at establishing the potential of fruit trees in carbon sequestration. The specific objectives were to establish the carbon stocks in fruit trees compare the potential of carbon stocks in citrus and mango trees and examine the relationship between the management practices and carbon stocks in fruit trees. At the farm level, plots were identified and transects established and individual fruit trees from sampled individual farms along the transect were selected. At the tree level, measurements of tree height and diameter at breast height were made. They were converted to biomass using allometric equations. Analysis of Variance was used to compare the differences in carbon stocks between the fruit trees and between the different management practices.  Findings revealed higher biomass and carbon stocks in mango trees as compared to citrus (74.57 ± 14.95 and 13.52 ± 1.25 t/ha respectively). Significant differences are also reported in carbon stocks under different management practices (p < 0.05). Irrespective of the species type, above-ground carbon under different management practices followed the order (from highest to lowest): Inorganic fertilizer < Intercrop < Monocrop < organic fertilizer and irrigation < intercrop and inorganic fertilizer.  The results also point out that mango fruits have a high potential to sequestrate carbon emissions hence mitigating global warming.